Quantum analytical modelling of threshold voltage for linearly graded alloy material gate recessed S/D SOI MOSFET - Malakar, Tiya Dey; Bhattacharyya, Partha; Sarkar, Subir Kumar (2017 Devices for Integrated Circuit (DevIC), 2017)
It has already been established that linearly graded alloy material gate recessed S/D SOI MOSFET is superior than the conventional SOI MOSFET structure due to its better device performance. However, only classical models are insufficient to establish the accurate potential profile or threshold voltage in nanoscale regime. Hence, in this paper Quantum Mechanical Effects (QME's) has been incorporated to develop an analytical model for threshold voltage. The 2-D Poisson's equation has been solved using necessary boundary condition to determine the complete nature of potential profile. The deviation of quantum threshold voltage has been calculated from classical one and these two are added to determine the final quantum threshold voltage. The analytical results are compared with the results of ATLAS 2D device simulator to validate our proposed quantum model.